PENGARUH CITRA MEREK, SOCIAL MEDIA MARKETING, DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN ES TEH INDONESIA CABANG TULUNGAGUNG - Vernanda Oktania Rahayu (Fakultas Ekonomi Universitas Tarumanagara, 2022)
This study aims to examine the effect of Brand Image, Social media marketing, and Word Of Mouth on Consumer Purchase Decisions of Indonesian Ice Tea Tulungagung Branch. This is related to the marketing strategy within the company, so that the company's performance is more optimal. The sampling technique in this study is a non-probability sampling technique with the Accidental Sampling technique. The number of respondents is 70.The results of the research on Brand Image, Social media marketing, and Word Of Mouth variables have a simultaneous influence on Purchase Decisions. Shown by the Fcount of 25,503 with a significant value of 0.000 < 0.05. This study shows that the variable Brand Image, and Word Of Mouth have a significant effect on purchasing decisions. The role of Social Media does not influence purchasing decisions at Es Teh Indonesia Tulungagung Branch. This happens because consumers are more inclined to the quality provided by Es Teh Indonesa Tulungagung Branch, as evidenced by positive and significant results on the Word Of Mouth variable